The National Youth Gang Survey: past, present, and future - Cahill, Meagan (The Oxford handbook of gangs and society, 2024)
From 1996 to 2012, the National Youth Gang Survey (NYGS), funded by the Office of Juvenile Justice and Delinquency Prevention, was conducted annually. The survey provided insight into gang trends in the United States, and researchers demonstrated its utility for studies on gang-related topics. Yet at the time of this writing, the survey had not been fielded for a decade. In 2020, the National Institute of Justice committed funding to revive the NYGS. This chapter reviews the history of the survey over the 17 years it was fielded, reviews its contributions to the field of gang research, and discusses plans for the revived NYGS. An updated NYGS will provide the field with a current understanding of risk factors for joining gangs, gang member behavior, and how to address gang problems. Part of the work will include increasing NYGS’s use for policymaking, informing practice, and rigorous research.